The Clout Chasing Phenomenon: When Sensual Disgrace on Instagram Becomes a Shortcut to Popularity - OK Dedy Arwansyah; Roynanda Sinaga (Universitas Medan Area, 2026)
Social media, especially Instagram, is a platform that influences individual behavior in building a digital presence. The phenomenon of clout chasing emerged as a strategy to gain attention and popularity through provocative content, including sensual nuances. This study uses a descriptive-analytical method with a qualitative approach to understand the meaning behind this behavior. The subject of the study is Instagram users who actively produce personal content with emotional nuances to increase social interaction. The results show that the need for existential validation and recognition drives oversharing behaviors that utilize platform algorithmic mechanisms. This phenomenon reflects the disintegration of social norms, in which privacy and decency are replaced by new standards oriented towards interaction and popularity. The conclusion of the study states that clout chasing creates a cycle of performativity that deepens social alienation, describing how social media influences an individual's morality and digital identity.